Bioremediation of Nitrate and Nitrite on the Rehabilitation of Contaminated Jatibarang Landfill and the Application of Calla Lily - Maria Ulfah; Octavia Devi Puspita Sari; Muhammad Syaipul Hayat (Postgraduate, University of Mataram, 2024)
Currently, waste processing is a problem because it is not yet optimal. The high content of nitrates and nitrites results in environmental pollution which can cause losses because it affects health and biodiversity. One effort to control environmental pollution is phytoremediation using calla lily (Zantedeschia aethiopica) to remediate nitrate and nitrite levels that do not comply with quality standards so that pollution can be minimized. This research aims to determine the effectiveness of calla lily as a phytoremediation agent for landfill leachate nitrate and nitrite. This experimental research method uses a Completely Randomized Design (CRD) which consists of three treatment levels, namely variations in calla lily biomass of 0 grams, 200 grams, and 400 grams with 3 repetitions, and measurements of nitrate and nitrite levels are carried out on day 1, day 2. 3, and 7. The results showed that the most optimal percentage reduction in leachate nitrate levels occurred in the P1 on the day 7, namely 45%, while the most optimal percentage reduction in leachate nitrite levels occurred in the P1 on the day 7, it was 53%. The final nitrate content after the research was in accordance with the quality standards of PP RI No.22 of 2021, while the leachate nitrite content after treatment still exceeded the quality standards of PP RI No.22 of 2021. Calla lily has the potential to reduce nitrate and nitrite levels due to landfill leachate pollution.